Identifikasi Serotipe dan Sensitivitas Antibiotik S. pneumoniae yang Dibawa Nasofaring Penderita Oma di Kabupaten Banyumas - Oviani, Miranti; Wahyono, Daniel Joko; Safari, Dodi (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2020)
The aims of this study are to detect S. pneumoniae carried by nasopharnyx of children in primary school (aged 6-12 years) that diagnosed with AOM, to identify sensitivity of S. pneumoniae to antibiotics. The design of this study is nonexperimental survey with the descriptive analysis. Sampling was conducted in September - December 2018 in Banyumas district primary schools. Detection of S. pneumoniae was performed with microbiology methods. Meanwhile, serotype was determined by multiplex PCR and sensitivity to antibiotics was deduced using disc diffusion. The result of this study showed that carriage rate of S. pneumoniae carried by nasopharynx in children aged over 5 years that diagnosed with AOM in the Banyumas district was 35%. Serotype of S. pneumoniae obtainend from this study were 6A/6B, 6C/6D, 17F, 3, 13, 14, 23B, and untypeable. In addition, isolates of S. pneumoniae were highly susceptible to clindamycin (100%), erythromycin (100%), sulphametaxazole/trimethoprim (100%), chloramphenicol (88%), oxacillin (77%), and tetracycline (66%).